DETECTION OF ANTIBIOTIC RESISTANCE AND CAPSULAR TYPES OF GROUP B STREPTOCOCCI ISOLATED FROM COLONIZED PREGNANT WOMEN - Paunović, Bojana; Kekić, Dušan; Kabić, Jovana; Gajić, Ina; Jovićević, Miloš (Medicinski podmladak, 2024)
Introduction: Group B streptococcus (GBS) is an opportunistic pathogen that colonizes the gastrointestinal and genital tract of 10-30% healthy people. GBS can cause early or late-onset disease manifested as pneumonia, sepsis, and meningitis. Penicillins are the first-choice therapy and prophylaxis of mother-to-child transmission. In the case of penicillin allergy, macrolides or vancomycin are used. The objective of this study was to determine antimicrobial susceptibility and macrolides resistance phenotypes of GBS isolated from vaginal swabs of pregnant women, as well as to determine capsular types (CPS) and identification of hypervirulent ST17 clone. Material and methods: From 1st January to 31st December 2021, 134 GBS isolates were collected. Identification was performed using conventional microbiological methods and molecular detection of species-specific dltR gene. The disk diffusion method was used to test antibiotic resistance according to EUCAST standard. Capsular typing was conducted by multiplex PCR method. A hypervirulent ST17 clone was identified by detection of the hvgA gene using PCR. Results: All isolates were sensitive to penicillin, vancomycin, and fluoroquinolones. Tetracycline resistance was the most common, detected in 81.3% (109/134) strains. Macrolide resistance was detected in 37.3% (50/134) of isolates, while 14.9% (20/134) showed resistance to high doses of gentamicin. Resistance to chloramphenicol was noticed in 1.5% (2/134) isolates. The most common macrolide resistance phenotype was cMLS (31/50, 62.0%). The most identified CPS were V found in 33 isolates (25.0%) and III identified in 30 strains (22.0%). A hypervirulent ST17 clone was detected in 12.7% (17/134) of isolates; 15 belonged to CPS III and 2 to CPS IV. Conclusion: The high frequency of macrolide resistance in group B streptococci isolated from colonized pregnant women is a severe public health concern. Also, the detection of many CPS III isolates and ST17 clones indicates the need for continuous screening and monitoring of the prevalence of GBS infections in pregnant women and neonates.